DNA vaccination induced protective immunity against SARS CoV-2 infection in hamsterss. - Kit Man Chai (Public Library of Science (PLoS), 2021)
The development of efficient vaccines against COVID-19 is an emergent need for global public health. The spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a major target for the COVID-19 vaccine. To quickly respond to the outbreak of the SARS-CoV-2 pandemic, a nucleic acid-based vaccine is a novel option, beyond the traditional inactivated virus vaccine or recombinant protein vaccine. Here, we report a DNA vaccine containing the spike gene for delivery via electroporation. The spike genes of SARS-CoV and SARS-CoV-2 were codon optimized for mammalian cell expression and then cloned into mammalian cell expression vectors, called pSARS-S and pSARS2-S, respectively. Spike protein expression was confirmed by immunoblotting after transient expression in HEK293T cells. After immunization, sera were collected for antigen-specific antibody and neutralizing antibody titer analyses. We found that both pSARS-S and pSARS2-S immunization induced similar levels of antibodies against S2 of SARS-CoV-2. In contrast, only pSARS2-S immunization induced antibodies against the receptor-binding domain of SARS-CoV-2. We further found that pSARS2-S immunization, but not pSARS-S immunization, could induce very high titers of neutralizing antibodies against SARS-CoV-2. We further analyzed SARS-CoV-2 S protein-specific T cell responses and found that the immune responses were biased toward Th1. Importantly, pSARS2-S immunization in hamsters could induce protective immunity against SARS-CoV-2 challenge in vivo. These data suggest that DNA vaccination could be a promising approach for protecting against COVID-19.